Semantic technology : 5th Joint International Conference, JIST 2015, Yichang, China, November 11-13, 2015, Revised selected papers /: 5th Joint International Conference, JIST 2015, Yichang, China, November 11-13, 2015, Revised selected papers. (2016) - Unknown
No abstract available